2017
DOI: 10.2196/jmir.7097
|View full text |Cite
|
Sign up to set email alerts
|

Use of GetCheckedOnline, a Comprehensive Web-based Testing Service for Sexually Transmitted and Blood-Borne Infections

Abstract: BackgroundThe British Columbia Centre for Disease Control implemented a comprehensive Web-based testing service GetCheckedOnline (GCO) in September 2014 in Vancouver, Canada. GCO’s objectives are to increase testing for sexually transmitted and blood-borne infections (STBBIs), reach high-prevalence populations facing testing barriers, and increase clinical STI service capacity. GCO was promoted through email invitations to provincial STI clinic clients, access codes to clients unable to access immediate clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 17 publications
0
45
0
Order By: Relevance
“…We completed semi-structured, one-to-one interviews with 37 key agents (HCP, administrators, policymakers, and community-based sexual health service providers) involved in GCO’s development. Another study explored the opinions and expectations MSM had of GCO during its development [ 14 ], and an analysis of users’ experiences with the pilot test of GCO in Vancouver indicated that 13% of clients who created GCO accounts were under age 25, suggesting that the program may need to be adapted or promoted in different ways to increase uptake amongst youth [ 32 ]. Interviews were conducted during the pre-implementation phase of GCO in Vancouver in 2013, prior to its launch in September 2014.…”
Section: Methodsmentioning
confidence: 99%
“…We completed semi-structured, one-to-one interviews with 37 key agents (HCP, administrators, policymakers, and community-based sexual health service providers) involved in GCO’s development. Another study explored the opinions and expectations MSM had of GCO during its development [ 14 ], and an analysis of users’ experiences with the pilot test of GCO in Vancouver indicated that 13% of clients who created GCO accounts were under age 25, suggesting that the program may need to be adapted or promoted in different ways to increase uptake amongst youth [ 32 ]. Interviews were conducted during the pre-implementation phase of GCO in Vancouver in 2013, prior to its launch in September 2014.…”
Section: Methodsmentioning
confidence: 99%
“…Of 72 unique publications identified in our original search, 14 studies [1819, 20*, 21*, 22*, 23*, 24*, 25*, 26*, 27*, 28*, 29, 30**, 31**,32*] met the inclusion criteria and were published between April 2015 and March 2017 (Table 1). Inclusion criteria included articles in English that reported data on impact of online interventions in increasing access to HIV and sexually transmitted infections (STIs) related information, reaching and engaging online key populations in HIV/STIs awareness and/or demonstrating testing and prevention services uptake.…”
Section: Online-to-offline (O2o) Modelsmentioning
confidence: 99%
“…Clients presented with the laboratory form to one of six designated sites in Vancouver where specimens were collected. Majority 73% of those who printed the lab forms actually submitted specimens [29, 30**]. The requirement to print a laboratory requisition was noted as a major barrier to service uptake and the study recommended barcode scanning from client’s smartphone as future alternative, similar to the strategy used in Thailand [28*].…”
Section: Types Of O2o Models In Hiv Service Deliverymentioning
confidence: 99%
See 2 more Smart Citations